#TITLE_ALTERNATIVE# - FADHILA SARI ( NIM : 15010042 ), ANNESA
Buckling Restrained Braced Frame (BRBF) system is an innovation of Concentrically Braced Frame (CBF) system that uses a reinforcement to accommodate and withstand compressive force which can cause buckling in steel. The analysis will compare the behavior and performance of CBF and BRBF structures, then compare it with the behavior of other structures with different braced configurations, Chevron-type and X-Two Story type. The methods are preliminary design, structure element design, pushover analysis, nonlinear time history analysis, and the performance comparison analysis of the structure. Capacity design is applied on beam and column elements design, based of cross-section braced profile capacity. Nonlinear time history analysis is done to see the behavior of the building when receive an cyclic loading caused by the earthquake. Pushover analysis is done to ensure that collapse sequence of the structure and structural performance is appropriate target. It shows that the structure is strong enough to endure the seismic loading.The analysis shows that the BRBF system will result in a smaller profile, lighter weight, has a strong ductility and larger overstrength after the melting point than CBF system. BRBF system also has a larger displacement because of its rigidity is smaller than CBF system. V type braced configuration of BRBF system has slightly lower performance than the Chevron-type and X-Two Story